Genomic variance in Yucatan pigs and detection of donor-derived cell-free DNA after heart transplantation - Michelle Mendiola Pla; Joseph A. Prinz; Kishen Mitra; Franklin H. Lee; Matthew F. Smith; Alejandro Alvarez Lobo; Carmelo A. Milano; Dawn E. Bowles; Devjanee Swain-Lenz (PLoS ONE, 2025)
Acute rejection, one of the most devastating complications that can occur following organ transplantation, is caused by antigenic differences between the organ donor and the recipient. Following cardiac transplantation, an estimated 12% of patients will experience at least one episode of moderate or severe acute rejection in the first year after transplantation. To better understand the genetic mechanisms underlying acute rejection, Yucatan pigs (YP) serve as an ideal preclinical model. Translatability of the YP preclinical model relies on the fidelity observed between preclinical and clinical pathologies. Cell-free DNA (cfDNA) analysis has emerged as a blood-based, non-invasive screening tool for acute rejection of solid organs following transplantation. We present a detailed characterization of the genomic variance in YPs. The degree of variance matches that observed in humans, enabling for the ability to detect and distinguish between donor-derived and recipient-derived fragments isolated from the transplant recipient’s blood.